An update of the list of types of Ceraphronoidea, Cynipoidea and "Proctotrupoidea" (Hymenoptera) housed at the Museo de La Plata, Argentina Una actualización de la lista de los tipos de Ceraphronoidea, Cynipoidea y "Proctotrupoidea" (Hymenoptera) depositados en el Museo de La Plata, Argentina - Díaz Norma Beatriz; Fabiana Edith Gallardo; Cecilia Beatriz Margaría; Marta Susana Loiácono (Revista de la Sociedad Entomológica Argentina, 2005)
In this paper we listed and examined four type specimens of Ceraphronoidea, 94 of Cynipoidea and 198 of "Proctotrupoidea" (Hymenoptera) housed at the Museo de La Plata, Argentina (División Entomología) not included in previous papers. We also provide update information on categories of types, data of collection and hosts for all cases. These types belong to one, 10 and 12 species respectively and the species were described by Martínez (1), Diaz (2), Diaz & Gallardo (3), Gallardo, Diaz & Marchiori (1), Gallardo, Diaz & Uchoa (1), Kerrich & Quinlan (1), Pujade-Villar & Diaz (1), Ros-Farré & Pujade-Villar (1), De Santis & Loiácono (9), Loiácono (2), and Loiácono & Margaría (1). Una actualización de la lista de los tipos de Ceraphronoidea, Cynipoidea y "Proctotrupoidea" (Hymenoptera) depositados en el Museo de La Plata, Argentina. En este estudio listamos y examinamos cuatro tipos de Ceraphronoidea, 94 de Cynipoidea y 198 de "Proctotrupoidea" depositados en el Museo de La Plata (División Entomología) no incluidos en trabajos previos. Para cada taxón se brinda la información actualizada acerca de los materiales tipo, datos de recolección y huéspedes. Estos tipos pertenecen a una, 10 y 12 especies respectivamente, las cuales fueron descriptas por Martínez (1), Diaz (2), Diaz & Gallardo (3), Gallardo, Diaz & Marchiori (1), Gallardo, Diaz & Uchoa (1), Kerrich & Quinlan (1), Pujade-Villar & Diaz (1), Ros-Farré & Pujade-Villar (1), De Santis & Loiácono (9), Loiácono (2), y Loiácono & Margaría (1).